PENGEMBANGAN KOMIK BERBASIS LITERASI SAINS PADA MATERI KEANEKARAGAMAN HAYATI BAGI SISWA KELAS X SMA - Ana Mandasari; Mariani Natalina; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to produce comic media based on science literacy onbiodiversity lesson for high quality class X senior high school students. This researchwas conducted at the Faculty of Teacher Training and Education Riau University,Public Senior High School 8 Pekanbaru and Public Senior High School 6 Pekanbaru inNovember-February 2021. The type of research used is Research and Development(R&D) with the ADDIE research model consisting of 5 stages, namely analysis, design,development, implementation and evaluation. In this research, it is limited only to thedevelopment stage. Data collection instruments in the form of validation sheets andquestionnaires of respondents. The results of the validation of comics based onscientific literacy on biodiversity lesson for students of class X senior high school are atan average value of 3,56 with a very valid category. The result of the limited test scoreare 3,42 with a very good category. Thus, comics based on scientific literacy onbiodiversity material for students of class X of senior high school have been successfullydeveloped with very good quality and can be implemented on a wider scale.Key Words: Comic, Scientific Literacy, Biodiversity